Pengaruh Green Product dan Green Innovation Terhadap Kinerja Organisasi Dimediasi Lingkungan Bisnis Pada Pariwisata Hijau - Hernum Daya Wati (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – Rapid changes in the business environment, especially from external factors, require business people to be able to choose and develop the right business. The right choice of business can lead to optimal organizational performance. Aim – The purpose of this study is to examine and analyze (1) the effect of green products on organizational performance; (2) the effect of green innovation on organizational performance; (3) the effect of green products on the business environment; (4) the effect of green innovation on the business environment; (5) the effect of the business environment on organizational performance; (6) the effect of green products on organizational performance through the business environment; (7) the effect of green innovation on organizational performance through the business environment. Design / methodology / approach – The respondents in this study were business actors and strategic decision makers in green tourism businesses located in Gresik Regency and Bojonegoro Regency. The analysis tool used was SEM with SmartPLS software. Findings – The results of the study indicate that green products and green innovation have a positive and significant effect on organizational performance, and green innovation has a positive and significant effect on the business environment. However, green products do not have a positive and significant effect on the business environment. The business environment also does not have a positive and significant effect on organizational performance. Meanwhile, the business environment fully mediates the effect of green products on organizational performance, and the business environment also fully mediates the effect of green innovation on organizational performance. Conclusion – (1) Green products can improve organizational performance, but cannot improve the business environment; (2) Good green innovation can improve organizational performance and the business environment; (3) The business environment cannot improve organizational performance; (4) The business environment cannot mediate the influence of green products on organizational performance; (5) The business environment cannot mediate the influence of green innovation on organizational performance. Research implication – (1) The results of this study indicate that business environment variables and organizational performance have the lowest average values compared to other variables, so the business environment, such as Volatility, Uncertainty, Complexity, and Ambiguity, faced by decision-makers in tourism needs to be further improved; (2) Decision-makers in tourism, for the most part, have innovative ideas that leverage the unique potential of each location; however, these innovations cannot be implemented due to the limited capital available to organizations. Therefore, in the future, the tourism sector must collaborate with investors by promoting its tourism potential. Limitations – (1) Future researchers need to consider a broader scope of research objects, both in the same object of green tourism and on a larger scale such as green entrepreneurship, in order to enrich the results and findings of the research; (2) This study only uses a few indicators to reflect the existing variables, so that future research can expand and integrate the research model by including several other indicators that are considered appropriate for the object taken.